Digital Financial Transformation and Operational Efficiency in Batik MSMEs - Laynita Sari (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The development of digital technology has driven significant changes in the operational management of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. In the context of the batik industry, digital transformation is a strategic step to improve cost efficiency and maintain competitiveness in the creative economy era. This study aims to analyze the digital transformation process and its impact on operational efficiency in Batik MSMEs in Cirebon. The research approach used is descriptive qualitative with a case study method. Data were collected through in-depth interviews, field observations, and documentation of five batik MSME players in the Trusmi area. The results showed that digital transformation was carried out through three main aspects: marketing digitalization, financial digitalization, and production digitalization. The implementation of digital technology is proven to reduce operational costs by 25-35%, accelerate cash flow, and increase the transparency of financial records. However, barriers are still encountered in digital literacy, organizational culture resistance, and infrastructure limitations. This research confirms that the success of MSMEs' digital transformation depends not only on technology, but also on the readiness of human resources and support related to the digital business ecosystem.